The Effects of Self-Efficacy-Based Fall Prevention Program among Elderly in Phibunmangsahan Town Municipality, Ubon Ratchathani Province, Thailand - Sukaree, Warunee; Sukhumal, Phandita; Limpiteeprakan, Pawena (GHMJ (Global Health Management Journal), 2025)
Background: Falls among the elderly remain a significant public health concern, particularly in rural areas where access to healthcare and fall prevention programs are limited. Aims: This study aims to evaluate the effectiveness of a self-efficacy-based fall prevention program in improving knowledge, muscle strength, mobility, and balance among elderly individuals at risk of falling in Phibunmangsahan Town Municipality. Methods: This quasi-experimental study included 60 elderly participants (aged 60-79) who were identified as being at risk of falling using the Thai Falls Risk Assessment Test (Thai-FRAT). Participants were randomly assigned to either an experimental group (n=30) or a control group (n=30). The experimental group received an 8-week fall prevention program based on self-efficacy theory, which included educational sessions, exercise interventions, and confidence-building strategies. Data collection was conducted using pre- and post-intervention questionnaires, physical assessments of muscle strength, mobility, and postural control, and statistical analysis was performed using paired t-tests and independent t-tests to evaluate the effectiveness of the intervention. Results: The results revealed that participants in the experimental group showed significant improvements in their knowledge of fall prevention (Meanbefore=11.33 (SD.=3.88), Meanafter= 11.90 (SD.=1.88), mobility (Meanbefore=12.63 (SD.=3.88), Meanafter= 10.27 (SD.=3.12), balance (Meanbefore=9.23 (SD.=2.67), Meanafter= 11.43 (SD.=3.19), and muscle strength (Meanbefore=8.97 (SD.=2.94), Meanafter= 11.43 (SD.=3.49), compared to their pre-intervention levels and the control group (p<0.05). The control group showed no significant changes in these variables. Additionally, there were no significant negative results observed during the study. Conclusion: The self-efficacy-based fall prevention program significant enhanced the knowledge, physical capabilities, and self-confidence of elderly participants, highlighting its potential as an effective intervention for fall prevention in community settings. This study recommends the implementation of similar programs in other rural areas to reduce fall-related injuries among the elderly, emphasizing the importance of integrating self-efficacy theory into fall prevention strategies.